1999
DOI: 10.1037/1082-989x.4.1.84
|View full text |Cite
|
Sign up to set email alerts
|

Sample size in factor analysis.

Abstract: The factor analysis literature includes a range of recommendations regarding the minimum sample size necessary to obtain factor solutions that are adequately stable and that correspond closely to population factors. A fundamental misconception about this issue is that the minimum sample size, or the minimum ratio of sample size to the number of variables, is invariant across studies. In fact, necessary sample size is dependent on several aspects of any given study, including the level of communality of the var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

70
2,648
6
109

Year Published

2003
2003
2018
2018

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 3,787 publications
(2,833 citation statements)
references
References 41 publications
70
2,648
6
109
Order By: Relevance
“…These authors argue against the use of invariant rules for determination of sample size for a CFA and instead, present a mathematical framework for computing the necessary sample size based on the size and variability of the obtained communalities and whether factors are overdetermined. In the case of the present data, with five or more items per factor, moderate to high expected communalities based on past exploratory factor analyses, and n = 182, the approximate value of the congruence coefficient (which reflects the degree of correspondence between sample and population factors) is .98, which is excellent within MacCallum et al▯s (1999) framework. Thus, the sample size in the present report is adequate for a CFA.…”
Section: Analytic Strategysupporting
confidence: 45%
“…These authors argue against the use of invariant rules for determination of sample size for a CFA and instead, present a mathematical framework for computing the necessary sample size based on the size and variability of the obtained communalities and whether factors are overdetermined. In the case of the present data, with five or more items per factor, moderate to high expected communalities based on past exploratory factor analyses, and n = 182, the approximate value of the congruence coefficient (which reflects the degree of correspondence between sample and population factors) is .98, which is excellent within MacCallum et al▯s (1999) framework. Thus, the sample size in the present report is adequate for a CFA.…”
Section: Analytic Strategysupporting
confidence: 45%
“…An adequate sample size depends on several different factors, including the number of classes, the restrictiveness of the within-class model, the withinclass model complexity, the quality of covariates, and the reliability of the observed data within class. This situation is not different from common factor analysis, in which MacCallum, Widaman, Zhang, and Hong (1999) have shown that simple rules of thumb for the minimum sample size needed for the recovery of factors are inappropriate because an adequate sample size depends strongly on characteristics of the variables and the study design. Note.…”
Section: Discussionmentioning
confidence: 94%
“…1). Of note for the focus of the present review, sample sizes of fewer than 45 participants are generally insufficient to fit common factor models (MacCallum, Widaman, Zhang, & Hong, 1999).…”
Section: Sample Sizesmentioning
confidence: 99%